Rijeka and Suroundings in Matoš’s Work - Sorel, Sanjin (Poznańskie Studia Slawistyczne, 2014)
The article discusses the relationship between A.G. Matoš and the city of Rijeka, which can be seen in his work „Oko Rijeke”. The focus of the analysis is in the ideology by which the discourse subject observes the city. From the viewpoint of patriotic ideology, the subject comments on the colonialist relations that occur at the time in Rijeka, but his idealization of patriotic culture, as opposed to „negative” historic, landscape and political status of the city, impede his ability to give an accurate insight. Therefore, his work is inclined to be more political than literary.